2018
DOI: 10.2478/crebss-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Croatian banking system total assets concentration dynamics: performing a variety of inequality measures

Abstract: The paper provides an overview of the trend in the concentration of the total assets of banks in Croatia for the period from 2007 to 2016 with the aim of analysing and presenting the changes that occurred in the system. Also, the paper shows the theoretical framework of the indicators used in the research as well as the comparison of their obtained values. The data used to calculate the total assets concentration are taken from the Croatian National Bank. The concentration indices used in the study include the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The Pietra-Hoover inequality index (PHI) is a peculiar measure (Delalić, et al, 2018) indicating the proportion of the total variable value which should be transferred from the value area above the arithmetic mean to the value area below the arithmetic mean such that a uniform distribution can be achieved. The value of this index can be found from the Lorenz curve: the value is obtained from the greatest "vertical distance" between the Lorenz curve and the uniform distribution line.…”
Section: Pietra-hoover Gini Wealth Inequality Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pietra-Hoover inequality index (PHI) is a peculiar measure (Delalić, et al, 2018) indicating the proportion of the total variable value which should be transferred from the value area above the arithmetic mean to the value area below the arithmetic mean such that a uniform distribution can be achieved. The value of this index can be found from the Lorenz curve: the value is obtained from the greatest "vertical distance" between the Lorenz curve and the uniform distribution line.…”
Section: Pietra-hoover Gini Wealth Inequality Distributionmentioning
confidence: 99%
“…In order to discuss gain inequality and team hierarchy, one can usefully calculate so called « concentration indices »: the entropy measure, the Theil entropy, the Gini coefficient, the Pietra index, the coefficient of variation, the Rosenbluth (Rosenbluth, 1955;Delalić et al, 2018), and first, the Hirschman-Herfindahl index.…”
Section: Specificity Of Professional Cyclism Sport Competitionmentioning
confidence: 99%
“…It can be concluded that the Croatian banking sector is characterised by an oligopolistic structure: it is polarised into a small number of large banks and a large number of small banks. It is necessary to keep in mind that high concentration in banking market can have negative effects on the system due to reduced competition, and apart from the fact that banks can form higher prices, there is also a problem of risk dispersion which can be dangerous for the financial stability of the country (Delalić, Čurković, & Antić, 2018).…”
Section: Literature Overviewmentioning
confidence: 99%